CONCEPT AND FEATURE OF LITERARY TRANSLATION (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
The article provides information about general notion and specific characteristics of literary translation. The article also analyses a few examples taken from “The old man and the sea”.